Effect of Black Soldier Fly (Hermetia Illucens) Maggots Meal as a Substitute for Fish Meal on Growth Performance, Biochemical Parameters and Digestibility of Broiler Chickens - Attivi , K.; Agboka, K.; Mlaga, G.K.; Oke, O.E.; Teteh, A.; Onagbesan, O.; Tona, K. (International Journal of Poultry Science, 2020)
Background and Objective: The scarcity and high cost of fish meal has led researchers to evaluate the use of unconventional protein sources as substitutes for fish meal in poultry feed. This study investigated the substitution of Black Soldier fly for fish meal in broiler diets. Materials and Methods: A total of 225 fourteen-day old broilers were assigned to five treatment groups: A0 (100% of fish meal and 0% of maggot meal), A25 (25% of fish meal and 75% of maggot meal), A50 (50% of fish meal and 50% of maggot meal), A75 (75% of fish meal and 25% of maggot meal) and A100 (0% of fish meal and 100% of maggot meal). Data were collected on feed intake, organ weights, biochemistry parameters and digestibility indices. Results: Birds in group A100 had the lowest feed intake and better feed conversion ratio. Gizzard weight of the birds in A0 and A25 was similar but significantly lower (p<0.05) than those in A50, A75 and A100. Intestinal length of birds in A50, A75 and A100 were significantly longer (p<0.05). No significant difference in serum total protein and cholesterol was recorded across the treatments whereas albumin concentration in the birds in group A100 was the highest (p<0.05). Triglycerides were in the following order: A0 = A25, = A50 A75 = A100. Uric acid concentration was significantly lower (p<0.05) in (A0). Conclusion: Black Soldier fly maggot meal improved broiler productive performance without any deleterious effect and can be considered as a suitable alternative for fish meal.